1997
DOI: 10.1007/bf01700416
|View full text |Cite
|
Sign up to set email alerts
|

Brucellar prosthetic arthritis in a total knee replacement

Abstract: The infecting pathogens most commonly implicated in prosthetic joint infections are staphylococci, streptococci, and gram-negative rods. Prosthetic infections caused by Brucella spp. are rarely described in the literature. Treatment of prosthetic infections remains complex and controversial, the most accepted course being antibiotic treatment with removal or retention of prosthetic components. The case of a 60-year-old man who developed Brucella septic arthritis of the right knee in a total knee replacement is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
0
21
0
2
Order By: Relevance
“…All patients who had been checked were strongly positive for Brucella specific serum tests. Nevertheless, this infection is very unusual in periprosthetic joint infection of the knee and only nine cases were reported in the literature (2,3,5,(17)(18)(19). In this case, if the authors had been aware of this infection, the serum indicators of brucellosis could have tested and the cultures incubated in a longer time period to detect the Brucella spp.…”
Section: Discussionmentioning
confidence: 95%
“…All patients who had been checked were strongly positive for Brucella specific serum tests. Nevertheless, this infection is very unusual in periprosthetic joint infection of the knee and only nine cases were reported in the literature (2,3,5,(17)(18)(19). In this case, if the authors had been aware of this infection, the serum indicators of brucellosis could have tested and the cultures incubated in a longer time period to detect the Brucella spp.…”
Section: Discussionmentioning
confidence: 95%
“…Systemic brucellosis is the most common clinical form of the disease but hematogenous spread may result in focal forms of infection. Endocarditis, glomerulonephritis, uveitis, splenic abscess, hepatic abscess, and prosthetic device infection all represent hematogenous spread of the infection [4][5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…According to Memish et al [3], more than 8,000 cases are reported per year to public health authorities. The mode of transmission is usually consumption of unpasteurized milk or infected dairy products or direct contact with livestock [4]. Breast involvement in animals is common, whereas in humans it is an extremely rare condition.…”
Section: Introductionmentioning
confidence: 99%
“…It is a systemic disease in which every organ can be affected [1]. Osteoarticular complications are common (up to 10%-85% of all cases) and can manifest as sacroiliitis, arthritis, spondylitis, osteomyelitis, tenosynovitis and borsitis [6][7][8].…”
Section: Discussionmentioning
confidence: 99%